MEASUREMENT OF ANTERIOR PELVIC TILT IN LOW BACK PAIN- AN OBSERVATIONAL STUDY - D, MALARVIZHI; Varma R, Sai Kishore; Vpr, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study was to measure the anterior pelvic tilt for both males and females of low back pain patients. Methods: Observational type. Procedure: Totally, 120 subjects were approached. In that 70 were males and 50 were females. Using i@handy application in mobile anterior pelvic tilt was calculated among low back pain patients. Results: Anterior pelvic tilt was increased in low back pain patients (male - 14.15Â° and female - 16.26Â°). In that correlation between males and visual analog scale (VAS) was not significant. However, there was a significant correlation found in female anterior pelvic tilt and VAS (p<0.01). Conclusion: This study concluded that there was an increase in anterior pelvic tilt among low back pain patients. Anterior pelvic tilt and VAS was highly correlated in females, not in males. Keywords: i@handy, Anterior pelvic tilt, Low back pain.